Assessing the choice of supplementary accommodation for the new normal urban areas in West Bengal, India - BATABYAL, DR. DEBASISH; CHATTERJEE, MR. PRATIM; PANDIT, DR. ABHIJIT; GOSWAMI, SHATRAJIT; KUMAR, DHARMENDER (The journal of contemporary issues in business and government, 2021)
Objectives: To measure the factors responsible for or contributing to the choice of accommodation in urban areas during and immediately after COVID 19 pandemic, with an increasing importance of location and its shifting perception for confidence building and future marketing. Method: Principal Component Analysis and Chi-Square tests are found useful for analyzing the primary data collected from the urban areas in West Bengal Results: COVID 19 risk perception and resultant behavior could not supersede purchasing power in the study area while location is playing a critical role. This study also projected a sustainability-safety-sustainability diaspora exhibiting future trends for supplementary accommodation sector with new-normal sustainability orientation in the area. Practical Implications: COVID 19 measures with more investments does not enhance confidence among urban dwellers in the study area, rather price and location play critical role with new COVID 19 orientation for supplementary accommodations. Social Implications: Risk perception, safety measures and actual availing of accommodation services are experiencing a wide gap as never before owing to this COVID 19 outbreak. This study focuses on this area with a future scope for supplementary accommodation. Value: This study redirects the future marketing, financial and entrepreneurial policy issues for supplementary accommodation sectors